The Effectiveness of Facebook Social Media Marketing in Photography Services Businesses (Study on Arie Photo Studio Wates' Facebook Account) - Kristanti, Desi; Mukhlis, Imam (Formosa Journal of Applied Sciences, 2023)
The research aims to determine the effectiveness of Facebook social media marketing in the wedding and pre-wedding event photography services business which is very interesting for consumers to pay attention to. This research method is descriptive qualitative research. The results of research using Facebook social media are very influential and effective because Facebook has features that support promotional activities, especially in the field of photography. With the existence of social media, it is easier for a business to be run to reach the wider community, Facebook social media is also very helpful in determining effective market segmentation in determining customers who need photographer services. There are obstacles for Arie Photo Studio in carrying out promotions on Facebook accounts that still have followers. It's still a bit difficult for photos uploaded by Arie Photo Studio to reach a wider community of Facebook users.